Effectiveness of Using KIA Books on Pregnant Women's Knowledge and Family Support in Facing Childbirth in Gowa - Amriani; Fitriani; Maqfirah (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2025)
Introduction The Maternal and Child Health Book (KIA) is a manual that contains information sheets and health service records as well as special notes if there are abnormalities in the mother during pregnancy, childbirth until postpartum as well as in children, namely fetuses, newborns, infants and children up to 6 years of age. This research aims to determine the effectiveness of using MCH books on pregnant women's knowledge and family support in dealing with childbirth. Method The type of research used is quantitative research with a correlative analytical design with a cross-sectional approach with a total of 30 samples collected randomly. Sampling using a questionnaire. Research results after analyzing the data using the Spearman Rank test, it was found that the value P = 0.640, so the P value> 0.05 means there is no relationship between the use of KIA books and the knowledge of pregnant women in dealing with childbirth. Then using the Chi-Square test, the P value = <0.001, so the P value <0.05 means there is a relationship between the use of KIA books and the family support of pregnant women in facing childbirth. Conclusion The use of MCH books is not effective for pregnant women's knowledge in facing childbirth, while the use of MCH books is effective for family support in facing childbirth.